Ocenjevanje prehranjenosti mladostnikov - Peklaj, Eva (Šport (Ljubljana), 2022)
Overweight and obesity are important public health problems in children and adolescents. Assessing the nutritional status of this population is very demanding due to the rapid growth, as a good understanding of all parameters of nutritional status is required, which are practically presented and explained in this paper. In the paper, we first present classic parameters such as body mass index and waist circumference, and then give an overview of newer parameters of nutritional status such as lean body mass index, fat mass index and phase angle. We hope that this brief review will be helpful to all physical education teachers, kinesiologists, sports coaches and those who work with children and in the field of sports.
Keywords: debelost; mladostniki; ocena stanja; otroci; prehranjevanje; šport; telesna aktivnost